The Hybrid Real-Time Dispatcher Training Simulator: Basic Approach, Software-Hardware Structure and Case Study; International Journal of Emerging Electric Power Systems; Vol. 20, iss. 1 - Suvorov A. A. Aleksey Aleksandrovich; Gusev A. S. Alexander Sergeevich; Ruban N. Yu. Nikolay Yurievich; Andreev M. V. Mikhail Vladimirovich; Askarov A. B. Alisher Bakhramzhonovich; Stavitsky S. A. Sergey Aleksandrovich (2019, 2019)
Title screen